Inside Cover: Modulation of Ultrafast Conformational Dynamics in Allosteric Interaction of Gal Repressor Protein with Different Operator DNA Sequences (ChemBioChem 7/2016). (1st April 2016) - Choudhury, Susobhan; Naiya, Gitashri; Singh, Priya; Lemmens, Peter; Roy, Siddhartha; Pal, Samir Kumar
Abstract : The inside cover picture shows an essential dance for the flow of life. A combined approach involving picosecond‐resolved FRET and polarization‐gated fluorescence was used to explore differential ultrafast dynamics in the allosteric interaction of Gal‐repressor protein dimer (GalR) with different operator‐DNA sequences, namely OE and OI . The observation of faster C‐terminal dynamics in the dimer upon N‐terminal recognition with OI compared to those with OE raises the possibility that the key ultrafast timescales of the protein fluctuations are involved in the allosteric regulation of tetramerization of the DNA‐bound dimers for a higher‐order nucleoprotein complex; this is likely to have functional consequences for regulating gene expression. More information can be found in the full paper by P. Lemmens, S. K. Pal et al. onpage 605 in Issue 7, 2016 (DOI:10.1002/cbic.201500657 ).